Diagnosis dan Tata Laksana Dispepsia - Abdul Jafar Sidik (PT Kalbe Farma Tbk., 2024)
Dyspepsia is commonly managed by general practitioners. The main symptom is a feeling of discomfort or heartburn and may be accompanied by a feeling of fullness, nausea, and vomiting. Dyspepsia can be divided into organic dyspepsia and functional dyspepsia. Management of dyspepsia starts from education, diet control, stress management, to drug therapy.